2017
DOI: 10.3389/fpls.2017.01398
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Identifies NBS-LRR-Encoding Genes Related with Anthracnose and Common Bacterial Blight in the Common Bean

Abstract: Nucleotide-binding site and leucine-rich repeat (NBS-LRR) genes represent the largest and most important disease resistance genes in plants. The genome sequence of the common bean (Phaseolus vulgaris L.) provides valuable data for determining the genomic organization of NBS-LRR genes. However, data on the NBS-LRR genes in the common bean are limited. In total, 178 NBS-LRR-type genes and 145 partial genes (with or without a NBS) located on 11 common bean chromosomes were identified from genome sequences databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
57
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 114 publications
8
57
3
Order By: Relevance
“…Hence, in recent years, use of GWAS for mapping economically important QTLs in agricultural crops has increased and P. vulgaris is not behind. Many QTLs having economic importance in common bean have been mapped using a GWAS approach ( Moghaddam et al, 2016 ; Wu et al, 2017 ; Kelly and Bornowski, 2018 ; Kamfwa et al, 2019 ; Bisneta and Gonçalves-Vidigal, 2020 ; Bornowski et al, 2020 ; Gonçalves-Vidigal et al, 2020 ; Mungalu et al, 2020 ). In the present study, significant differences observed in NW Indian bean genotypes led to the identification of SNPs associated with the anthracnose resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, in recent years, use of GWAS for mapping economically important QTLs in agricultural crops has increased and P. vulgaris is not behind. Many QTLs having economic importance in common bean have been mapped using a GWAS approach ( Moghaddam et al, 2016 ; Wu et al, 2017 ; Kelly and Bornowski, 2018 ; Kamfwa et al, 2019 ; Bisneta and Gonçalves-Vidigal, 2020 ; Bornowski et al, 2020 ; Gonçalves-Vidigal et al, 2020 ; Mungalu et al, 2020 ). In the present study, significant differences observed in NW Indian bean genotypes led to the identification of SNPs associated with the anthracnose resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the plant disease resistance genes belong to the NBS-LRR class and play a significant roles in plant disease resistance ( Jones and Dangl, 2006 ; Padder, 2014 ). The common bean genome also contains NBS-LRR regions that are distributed across all chromosomes ( Ferrier-Cana et al, 2003 ; Richard et al, 2017 ; Wu et al, 2017 ) and a recent GWAS study showed associations between these NBS-LRR regions with anthracnose resistance ( Wu et al, 2017 ). Anthracnose resistance genes Co-3 and its alleles, Co-16 are mapped to common bean Pv04 and this study also found association of SNPs on Pv04 with anthracnose resistance to races 3, 87, and 503 ( Geffroy et al, 1999 ; David et al, 2008 ; Coimbra-Gonçalves et al, 2016 ; Murube et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAB carries the dominant allele Asp, which confers the intense glossy aspect of the seed coat, while SAF has a dull seed coat [12] (Figure 1A). This gene is known to be located in chromosome 7 [15], where genes associated with anthracnose and angular leaf spot resistance [16,17], common bacterial blight [17] and nodulation [18] are also located.…”
Section: Genetic Control Of Seed Glossinessmentioning
confidence: 99%
“…However, to our knowledge, transcriptomic studies during X. phaseoli pv. phaseoli infection are limited to a cDNA-AFLP analysis [46] and qRT-PCR assays focused on R genes [47,48]. Previous work using X. phaseoli pv.…”
Section: Introductionmentioning
confidence: 99%